A Survey on the requirements elicitation practices among courseware developers - Kasirun, Z.M. (2005)
Requirements elicitation in any application development has many important benefits. Due to this, it should be practiced in alignment to its objectives. This paper is based on the findings of a survey conducted among Malaysian courseware developers community. The paper starts with a definition of requirements elicitation and a description on how the survey was conducted. This is followed by the requirements elicitation practice as perceived by the respondents. Finally, a conclusion is drawn on the requirements elicitation practices and how to improve them.